DIVIDEND POLICY, CORPORATE GOVERNANCE AND EARNINGS QUALITY: A CASE OF NON-FINANCIAL LISTED FIRMS OF PAKISTAN - Afzal, Tehmina; Siddiqui, Atif Atique; Khan, Shiraz; Khan, Muhammad Kamran; Huseen, Nader (Humanities & Social Sciences Reviews, 2021)
Purpose of the study: This research empirically examined the impact of the dividend policy and corporate governance attributes (board size, board meetings, audit quality, nomination committee, board independence, remuneration committee, and CEO duality) on earnings quality (EQ) of the firms in Pakistan. Methodology: The study used secondary data of 148 non-financial listed companies of the Pakistan Stock Exchange (PSX) with 1450 firm-year observations over 10 years from 2010 to 2019. Earning quality was assessed by the earnings management, while the values of the discretionary accruals were used to measure earnings management by employing the Modified jones model (1995). Panel regression analysis examined the impact of independent variables (dividend policy & characteristics of CG) on the dependent variable (EQ). Main Findings: Results revealed that the dividend policy showed no significant impact on earnings quality. Also, the results indicated that the audit quality and remuneration committee have a significant negative impact on earning management and a positive impact on earning quality. However, the results illustrate that the large board size, board meetings, CEO duality, firm size, and leverage have a positive influence on earnings management and a negative impact on earnings quality. Overall the study found that the corporate governance characteristics, firm size, and leverage influence the earnings quality of the firms in Pakistan. Applications of this study: The empirical results of the study will help to improve the understanding of dividend policy & corporate governance attributes in relationship with the EQ. Second, as dividend is considered one of the most important factors influencing investment decisions, so this endeavour will clarify to the investors and regulators that whether dividend will predict the quality of earnings in Pakistani firms. Novelty/Originality of this study: This study extends the literature of earnings quality that is very thin in Pakistan.